Використання планувальника завдань у роботі викладача ЗВО - Баран, Віталій; Марковець, Олександр (Видавництво Львівської політехніки, 2025)
Efficient time management is essential for modern university educators whose responsibilities span teaching, research, and administrative duties. Planning tools help structure various tasks, ensure timely completion of academic and organizational work, and thus improve productivity and well–being. This paper analyzes why educators need structured planning, outlines general types of planning tools (analog and digital), and highlights the multifaceted role of university teachers. Emphasis is placed on how systematic scheduling can improve efficiency and reduce stress.
Keywords: тайм–менеджмент; навчальне навантаження; навчальний розклад; засоби планування; ефективність; управління стресом